2017
DOI: 10.3390/jcdd4010002
|View full text |Cite
|
Sign up to set email alerts
|

Collagenolytic Activity Is Associated with Scar Resolution in Zebrafish Hearts after Cryoinjury

Abstract: Myocardial infarction is the major cause of cardiac injury in western countries and can result in a massive loss of heart cells, leading eventually to heart failure. A fibrotic collagen-rich scar may prevent ventricular wall rupture, but also may result in heart failure because of its stiffness. In zebrafish, cardiac cryoinjury triggers a fibrotic response and scarring. Unlike with mammals, zebrafish heart has the striking ability to regenerate and to resolve the scar. Thus, understanding the mechanisms of sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
(46 reference statements)
1
27
0
Order By: Relevance
“…Based on various previous reports, it is now possible to describe the dynamic series of events that occur during heart regeneration following cryoinjury (where a scar is formed in a similar manner to that during mammalian myocardial infarction), as comprising 3 main phases. These are: 1) the inflammation phase, which occurs during the first 7 dpc; 2) the collagen deposition phase, which takes place from 7 dpc to14 dpc; and 3) the tissue remodeling and scar resolution phase, which occurs from 14 dpc to 60 dpc 5 , 17 , 20 , 22 . Here, we investigated if the enzymatic activity of MMPs might be essential for zebrafish heart regeneration following cryoinjury, especially with regards to the inflammatory phase during the first 7 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on various previous reports, it is now possible to describe the dynamic series of events that occur during heart regeneration following cryoinjury (where a scar is formed in a similar manner to that during mammalian myocardial infarction), as comprising 3 main phases. These are: 1) the inflammation phase, which occurs during the first 7 dpc; 2) the collagen deposition phase, which takes place from 7 dpc to14 dpc; and 3) the tissue remodeling and scar resolution phase, which occurs from 14 dpc to 60 dpc 5 , 17 , 20 , 22 . Here, we investigated if the enzymatic activity of MMPs might be essential for zebrafish heart regeneration following cryoinjury, especially with regards to the inflammatory phase during the first 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is known that elevated collagenolytic activity starts 14 dpc, but by 30 dpc the level of activity is much reduced. In contrast, the expression level of various MMP transcripts are known to peak at 3 dpc, but they have declined by 7 dpc, and have returned to basal levels by 14 dpc 20 . It was thus suggested that type-I collagenases might play a role during the early phases of injury, namely the inflammation and scar formation periods.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This increase in collagenolytic activity coincides with the increased expression of several matrix metalloproteinases. Specifically, they found that mmp2 and mmp14a expression is significantly upregulated at 14 and 30 dpi, concomitant with the onset of scar clearance (Gamba, Amin‐Javaheri, Kim, Warburton, & Lien, ). It remains to be determined whether the same cells that synthesize collagen are also responsible for matrix degradation.…”
Section: Dynamics Of Zebrafish Heart Regenerationmentioning
confidence: 99%
“…For these reasons, zebrafish could help in the comprehension of pathophysiological MMPs processes post-MI in order to develop novel therapeutic targets able to inhibit specific MMP actions and, as a consequence, to limit the appearance of heart failure post-MI. Particularly, Gamba, et al demonstrated that, following cryoinjury, transcripts of matrix metalloproteinase genes, mmp2 and mmp14 , and Mmp2 enzymatic activity are increased, suggesting the involvement of these proteases in collagen degradation (43).…”
mentioning
confidence: 99%